0412 Parents Sleep Longer When School is Out for the Summer: Associations Among Parenthood, Gender, and Season. (27th May 2020) - Ruder, M; Rus, H M; Raj, A; Gahan, L; O'Mullane, B; Danoff-Burg, S; Weaver, M; Raymann, R
Abstract: Introduction: Seasonal effects in sleep are often attributed to day length; however, change in obligatory daily activities might also have an impact on sleep behavior. Longitudinal measurement using consumer sleep technology enables the observation of patterns in sleep behavior in the home environment. We analyzed the impact of parenthood and gender on total sleep time (TST) over the summer break period using data collected in the home. Methods: Sleep data were collected using the SleepScore mobile application from October 2018 through October 2019, with the summer break period defined as June 25th - August 5th. U.S. age and gender matched samples of parents and non-parents were selected using Mahalanobis distance from a pool of users more likely to have school-aged children. The final samples included n=345 parents (38.7 +/- 4.5 years) and n=345 non-parents (37.8 +/- 4.7 years); both groups were 46% female. Only weeknights (n=34, 323) were analyzed to maximize impact of school schedule. Linear regression and independent t-tests were used to analyze main and interaction effects for gender, parenthood, and summer break. Results: Male gender, parenthood, and summer break were associated with decreased sleep duration (ps < .01). However, during summer break, parents exhibited an increase in TST, with mothers (+5.6 mins) having a greater increase than fathers (+1.1 mins). In contrast, adults without children showed a decrease in TST during summer break, with males having a greater reduction (-8.8 mins) than females (-6.5 mins). Conclusion: These results suggest that parental status may play a part in seasonal sleep patterns. Contrary to the typical trend of shorter TST during summer, being a parent is associated with longer TST during summer break, with a greater increase for females. This change may be attributed to parents following a less rigid schedule when their children are not in school. Support: N/A